The Effect of Anchovy Stelophorus commersonii on Salivary Mutans Streptococci - Suherwin Mangundjaja; Ariadna Djais; Harun Asyiq Gunawan (Faculty of Dentistry, Universitas Indonesia, 2013)
Objectives: A clinical trial was carried out to investigate the inhibitory effect of Achovy of Stelophorus commersonii on the growth of salivary mutans streptococci over one week period. Methods: Before enrolled in the study, respondents filled and signed the informed consent. Twenty respondents participated in the study I, conducting two times of treatment as follows: twenty as treatment group before and after consuing anchovy of commersonii and the twenty subjects as control group before and after consuming non-anchovy of commersonii. Saliva samples were collected before and after consuming anchovy of commersonii and with a non-anchovy of commersonii. A serial dilution was made, followed by inoculating on TYS20B medium (Schaeken, et al, 1986). Data were obtained from colony forming units of salivary mutans streptococci grew on the TSY20B medium before and after consuming anchovy of commersonii were analyzed in a descriptive and t test. Results: showed that there was no significant difference in the average amount of Streptococcus mutans both between before and after consuming non-anchovy of commersonii. However, a significant difference was found respectively as results before and after consuming anchovy of commersonii. Conclusion: Anchovy of commersonii has an antimicrobiala ctivity against local strains of S. mutans isolated from human harbouring species. Long term consumption Anchovy fish of commersonii can be beneficial in preventing caries. DOI: 10.14693/jdi.v16i3.101